2015
DOI: 10.14238/pi55.5.2015.06
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D and vitamin D receptor gene FokI polymorphisms in children with tuberculosis

Abstract: Background Vitamin D deficiency and vitamin D receptor (VDR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The included studies were published between 2012 and 2017. Four studies [2023] described the difference in 25(OH)D levels in children with TB and controls; two [21,23] of these studies calculated 25(OH)D levels in nmol/L, and two [20,22] calculated 25(OH)D levels in ng/mL. Four studies [2427] evaluated the association between the presence of any TB and VDD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were published between 2012 and 2017. Four studies [2023] described the difference in 25(OH)D levels in children with TB and controls; two [21,23] of these studies calculated 25(OH)D levels in nmol/L, and two [20,22] calculated 25(OH)D levels in ng/mL. Four studies [2427] evaluated the association between the presence of any TB and VDD.…”
Section: Resultsmentioning
confidence: 99%
“…One study [25] showed a significant association between the presence of any TB and VDD, while 2 studies [24,25] showed a significant association between the presence of active TB and VDD; however, 3 studies [24,26,27] showed a nonsignificant association between the presence of any TB and VDD. Four studies [22,23,28,29] showed that VDD contributes to TB.…”
Section: Resultsmentioning
confidence: 99%